Efficacy and safety of Camosunate for the treatment of uncomplicated malaria in the University of Benin Teaching Hospital, Benin City, Nigeria - Damien Uyagu; Augustine Omoigberale; Paul Dienye (Healthcare in Low-resource Settings, 2013)
In Nigeria, nearly 110 million clinical cases of malaria are diagnosed per year, thus being a major public health problem. The problems of resistance resulted in the introduction of the artemisinin based combinations (ACT) by the WHO. Artesunate and amodiaquine (AS+AQ) is at present the world’s second most widely used ACT. This study is an assessment of the efficacy and safety of Camosunate (a brand of AS+AQ; Geneith Pharmaceutical Ltd., Oshodi, Lagos) in the treatment of uncomplicated malaria conducted at the University of Benin Teaching Hospital (UBTH). A cross-sectional assessment of the efficacy and safety of Camosunate was conducted over a period of one year using 120 patients selected after stratification, by random sampling technique. All recruited patients had slide-proven uncom- plicated malaria and were followed up for 28 days on commencement of Camosunate. Data was collected using a structured interviewer- administered questionnaire and was analysed using SPSS version 15. The overall efficacy of Camosunate was found to be 95.8%. Treatment was well tolerated as testified by the fact that there was no case withdrawal due to adverse drug reaction (ADR) or treatment emergent signs and symptoms (TESS). Also no evidence of toxicity was recorded. Camosunate is highly efficacious and well tolerated in this area of Nigeria and justifies its use as a first line treatment for uncomplicated malaria.